Influência da contaminação combinada de dextrana e amido na cristalização do açúcar - Merheb, Graciela de Amaral (Universidade Federal de São Carlos, 2014)
Introduced during the colonial period in Brazil, nowadays sugar cane is one of the main crops of the country's economy, generating more than 2 billion dollars per year in the Brazilian trade balance. Despite the benefits of expanding the sugarcane sector every year, the environmental impacts caused by burning straw cane sugar made the State of São Paulo Government create the Protocol of Agro-Environmental Cooperation in 2007, which aims the total elimination of cane burning by 2017. However, when the sugar cane stops being burned, some components of the plant, which remained in the field due to the burning, will start being in larger quantities in the process, and the effects of this future reality in sugar quality have not been studied In this doctoral thesis, the two components of great impact on the specifications or quality of the sugar were chosen: starch and dextran which were studied in the crystallization unit operation (by controlled cooling and vacuum evaporation), so that the impact on the final product (sugar) were evaluated. This current study used a reponse surface methodology, with 2 levels (309 and 1062 ppm), two factors (dextran and starch), 3 center points (one central point in triplicate) and 4 axial points, totaling 11 trials per type of crystallization. The experiments were conducted with sugar Type 2 solutions contaminated with starch and dextran, in an agitated and jacketed crystallizer (8 liters) in the laboratory. When the crystallization was performed, the matters were centrifuged, the sugars were separated from the honeys, and forwarded to the physico-chemical, textural and optical microscopy analyzes. In relation to the physicochemical analyzes of sugar, starch and dextran contamination interfered directly in the responses: starch, dextran, color, turbidity and alcoholic floc in both crystallization techniques, however, the controlled cooling under the same conditions of contamination (0-2000 ppm), presented sugars to lower rates, which kept the product according to the market specifications. The results of grain size analysis showed frequency curves with accumulation of smaller crystals at the opening of 0.5 mm, according to the increase of dextran in the tests. And the optical microscopy analysis identified the existence of a relationship between the amount of contaminants, and the appearance of agglomerated crystals, besides "needle-like" crystals were not observed. The experimental chosen design collaborated in the identification of starch and dextran agents, in the increase or decrease of the analyzed responses, besides suggesting the collaboration of the combined effect on the quality of sugar. Concerning the product quality, the use of crystallization technique by controlled cooling proved to be the most suitable in the reduction of contaminants in the sugar, particularly in solutions containing 2,000 ppm of dextran and starch. Given the crop of sugarcane in the coming years, and that the contamination of dextran and starch may be higher than those found in syrups of industrial processes currently, this work may contribute to the knowledge of the contaminants and their combined actions in the crystallization and in understanding of the differences in the product quality.
Keywords: Cristalização; Açúcar; Dextrana; Amido; Cana-de-açúcar; Cristalização por evaporação a vácuo; Cristalização por resfriamento controlado; Cozimento; Contaminações; Cana crua; Sugar crystallization by vacuum evaporation; Crystallization by controlled cooling; Cooking; Contamination; Dextran; Starch; Raw sugar cane; ENGENHARIAS::ENGENHARIA QUIMICA